2018
DOI: 10.1186/s12871-018-0525-5
|View full text |Cite
|
Sign up to set email alerts
|

Does implementation of an enhanced recovery after surgery program for hip replacement improve quality of recovery in an Australian private hospital: a quality improvement study

Abstract: BackgroundEnhanced recovery after surgery programs may improve recovery and reduce duration of hospital stay after joint replacement surgery. However, uptake is incomplete, and the relative importance of program components is unknown. This before-and-after quality improvement study was designed to determine whether adding ‘non-surgical’ components, to pre-existing ‘surgical’ components, in an Australian private healthcare setting, would improve patient recovery after total hip replacement.MethodsWe prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“… 115 In a prospective before-and-after study, introduction of standardized multimodal, opioid sparing analgesia, and general PONV prophylaxis significantly decreased the risk PONV. 116 …”
Section: Application Of Ponv Guidelines To Enhanced Recovery Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“… 115 In a prospective before-and-after study, introduction of standardized multimodal, opioid sparing analgesia, and general PONV prophylaxis significantly decreased the risk PONV. 116 …”
Section: Application Of Ponv Guidelines To Enhanced Recovery Pathwaysmentioning
confidence: 99%
“…115 In a prospective before-and-after study, introduction of standardized multimodal, opioid sparing analgesia, and general PONV prophylaxis significantly decreased the risk PONV. 116 Similarly in breast surgeries, effective postoperative analgesia techniques including paravertebral block (PVB) or pectoral nerves block (PECs) can reduce the risk of PONV; [117][118][119] and should be used in addition to nonopioid analgesia and multimodal PONV prophylaxis. [120][121][122] Head and neck surgeries are considered high risk for the development of PONV, and a recent clinical trial has demonstrated that preoperative assessment and multimodal prophylaxis are effective in reducing the risk of PONV.…”
Section: Application Of Ponv Guidelines To Enhanced Recovery Pathwaysmentioning
confidence: 99%
“…A minimum 8-point difference in QoR15 is regarded as clinically significant 14. Based on a study of hip arthroplasty patients,15 the median (IQR) for controls is assumed to be approximately 107 (85–123). Since the follow-up period is short, it is assumed that there will be minimal missing data over the course of the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Some patients feel reticent about new practices out of either ignorance or fear, so they disagree or need time to decide. The interdisciplinary team should answer each question of the patient and give them the written protocol instructions[ 16 , 20 , 21 ].…”
Section: Pre-operative Periodmentioning
confidence: 99%
“…According to ERAS protocols, there are several components of perioperative care that affect stress response and accelerate recovery. These include pre-surgical counselling, short fasting period, early mobilization, bowel and bladder preparation, anesthesia and analgesia, thrombocytopenia, prevention of nausea and vomiting and fluid management[ 20 ].…”
Section: Introductionmentioning
confidence: 99%